Ecofeminism In Zainab Novel By Husain Haikal - Cahya, Intan Aulia; Zawawi, Moh. (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research aims to find out the elements of ecofeminism in the novel Zainab by Husain Haikal and the relation of women through nature in the perspective of Ecofeminism. Nature basically has an important role in the survival of living things, especially humans. Nature is considered a producer that can provide results to support the progress of an ecosystem and personal needs. The study of ecofeminism talks about the elements of the relationship between nature and women in a literary work such as a novel or others. The method used in this research is descriptive qualitative, the primary source in this research is a novel entitled Zainab by Husain Haikal, while the secondary source is a previous study similar to the theory of ecofeminism. Data collection techniques in this research use document analysis techniques; read and record, while data analysis techniques use the Miles and Huberman model which consists of three stages, namely data reduction, data presentation and conclusion drawing. The results of this study show that women and nature have a pure closeness from the point of view of Ecofeminism. The representation of human closeness to nature is found in the form of exploitation of women, patriarchal power and the relationship between nature and women.